Image histogram and FFT based critical study on noise in fluorescence microscope images - Mkayes, A.A. (Institute of Electrical and Electronics Engineers Inc., 2017)
The immune system is a complex network of highly specialized cells (such as lymphocytes) and organs. All of these cells work together to reduce infection (antigens) such as bacteria, virus or tumor cell from the body. Biologic Response Modifiers (BRM) also known as immunotherapy, is a type of treatment which mobilizes and triggers the immune system of the body. This research work provides a description of noise nature of immunofluorescence microscope images. Thus, the study leads to determine the type of noise and choose the filter which best fit the noise presented in fluorescence microscope images. Image histogram and Fast Fourier Transform (FFT) have been applied on blood samples. However, the results show that the Gaussian noise is found in this kind of images. CLAHE filter has been applied to these images. The results obtained from CLAHE demonstrate the ability for this filter to deal with this kind of images. © 2016 IEEE.